1999
DOI: 10.1152/ajpheart.1999.277.4.h1609
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibition improves cardiac NE uptake and attenuates sympathetic nerve terminal abnormalities in heart failure

Abstract: Cardiac sympathetic nerve terminal dysfunction plays an important role in the downregulation of myocardial beta-adrenoceptors in heart failure. To determine whether chronic angiotensin-converting enzyme (ACE) inhibition improved cardiac sympathetic nerve terminal function and hence increased myocardial beta-adrenergic responsiveness, we administered ACE inhibitors to dogs with chronic right-sided heart failure (RHF) produced by tricuspid avulsion and pulmonary artery constriction. The RHF animals exhibited flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
3
24
0
1
Order By: Relevance
“…Himura et al (1993) observed under the same conditions a chamber-speci®c loss of noradrenergic nerve terminals, as evidenced by a reduction in catecholaminergic histo¯uorescence-and tyrosine hydroxylase-immunoreactive pro®les. The same group recently showed that chronic ACE inhibition attenuated these reductions of the noradrenaline clearance system possibly due to a protective e ect of ACE inhibitors on the sympathetic nerve terminal integrity and function (Kawai et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Himura et al (1993) observed under the same conditions a chamber-speci®c loss of noradrenergic nerve terminals, as evidenced by a reduction in catecholaminergic histo¯uorescence-and tyrosine hydroxylase-immunoreactive pro®les. The same group recently showed that chronic ACE inhibition attenuated these reductions of the noradrenaline clearance system possibly due to a protective e ect of ACE inhibitors on the sympathetic nerve terminal integrity and function (Kawai et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…First, it was recently shown that ACE inhibitors increase uptake-1 in heart failure (Kawai et al, 1999) and hypertension (Raasch et al, 2001), and second, ANG enhances catecholamine release via stimulation of presynaptic AT 1 receptors (Brasch et al, 1993;Balt et al, 2001a), so that AT 1 antagonists were able to diminish noradrenaline overflow in various in vitro and in vivo models (Dominiak et al, 1987;Minatoguchi et al, 1992;Dendorfer et al, 1998;Hä user et al, 1998;Balt et al, 2001a,b). However, it should be emphasized that the reversible or irreversible MAO inhibitors viloxazine or pargyline were found to increase biogenic amines in brains and livers due to their MAO inhibitory effects, underlining the importance of MAO for regulating tissue catecholamines (Martinez et al, 1986;Raasch et al, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic significance of this action was revealed for the treatment of heart failure where a pathological sympathetic stimulation was associated with decreased cardiac noradrenaline levels (Regitz et al, 1991) due to an impairment of neuronal catecholamine uptake (Böhm et al, 1995). Kawai et al (1999) were the first to demonstrate that cardiac noradrenaline content in heart failure is increased by ACE inhibitors due to an enhanced cardiac neuronal uptake of noradrenaline; this should reflect one of the cardioprotective mechanisms of ACE inhibitors. Similar conditions appear to exist in hypertension where ACE inhibitors improved cardiac noradrenaline uptake-1 (Raasch et al, 2001).…”
mentioning
confidence: 99%
“…31 Reversely, an observed enhancement of NET during experimental or therapeutic AT 1 blockade or angiotensin-converting enzyme inhibition strengthens our hypothesis of a presynaptic interaction between AT 1 receptors and NET. 12,13,32,33 However, noradrenaline uptake alone is not sufficient to explain all of the vascular desensitization by losartan. As discussed, ␣ 2 -adrenoceptors may contribute by modulating the endogenous release of noradrenaline during NET blockade.…”
Section: Discussionmentioning
confidence: 99%
“…9 On the other hand, there is evidence that an increase in vascular noradrenaline sensitivity by Ang II may be attributed to a reduction of catecholamine clearance, because Ang II diminishes neuronal catecholamine uptake. [11][12][13] We therefore hypothesized that blockade of AT 1 receptors might enhance catecholamine uptake and consequently attenuate noradrenaline-induced vasoconstriction. To verify this hypothesis, we endeavored to confirm a reduction of noradrenaline reactivity during AT 1 blockade and to determine the role of sympathetic innervation in this effect.…”
mentioning
confidence: 99%